Folate-conjugated gene-carrying microbubbles with focused ultrasound for concurrent blood-brain barrier opening and local gene delivery. (November 2016) - Fan, Ching-Hsiang; Chang, En-Ling; Ting, Chien-Yu; Lin, Yu-Chun; Liao, En-Chi; Huang, Chiung-Yin; Chang, Yuan-Chih; Chan, Hong-Lin; Wei, Kuo-Chen; Yeh, Chih-Kuang
Abstract: Previous studies have demonstrated that circulating DNA-encapsulated microbubbles (MBs) combined with focused ultrasound (FUS) can be used for local blood-brain barrier (BBB) opening and gene delivery. However, few studies focused on how to increase the efficiency of gene delivery to brain tumors after the released gene penetrating the BBB. Here, we proposed the use of folate-conjugated DNA-loaded cationic MBs (FCMBs). When combined with FUS as a trigger for BBB opening, FCMBs were converted into nanometer-sized vesicles that were transported to the brain parenchyma. The FCMBs can selectively aggregate around tumor cells that overexpressed the folate receptor, thus enhancing gene delivery via folate-stimulated endocytosis. Our results confirmed that FCMBs can carry DNA on the surface of the MB shell and have good targeting ability on C6 glioma cells. In addition, the optimized FUS parameters for FCMBs-enhanced gene delivery were confirmed by cell experiments (center frequency = 1 MHz; acoustic pressure = 700 kPa; pulse repetition frequency = 5 Hz; cycle number = 10000; exposure time = 1 min; FCMBs concentration = 4 × 10 7  MB/mL). In vivo data also indicated that FCMBs show better gene transfection efficiency than MBs without folate conjugation and the traditional approach of directly injecting the gene. This study described our novel development of multifunctional MBs for FUS-triggered gene delivery/therapy.